New solenofilomorphids (Solenofilomorphidae: Acoela) from the northwest Atlantic - Hooge, Matthew D.; Todt, Christiane; Tyler, Seth (Zootaxa, 2025)
Myopea calleum sp. nov. and Solenofilomorpha crezeei sp. nov. are newly discovered species of interstitial acoels and the first species of the acoel family Solenofilomorphidae to be described from the NW Atlantic. Both species have rather robust reproductive organs compared to their congeners. M. calleum sp. nov. is distinctive for its prominently glandular penis encompassed in an elongate, thick-walled seminal vesicle readily visible in squeeze preparations, as well as for its red coloration and lateral chordoid tissue. S. crezeei sp. nov. is similarly distinct from other species of Solenofilomorpha in having a more muscular, thick-walled seminal vesicle and thick, muscular sheath enclosing both seminal vesicle and penis, but also in having a sclerotized cone capping the penis. The cone is formed by converging necks of actin-rich cells encircling the muscular sheath where it joins the antrum.